Ergonomic considerations on the activity of the hospital emergency and urgent unit management (Human Factors in Design, 2024)
The study proposes to identify the main demands faced by the head of the urgency and emergency unit of a university hospital in Santa Catarina, focusing on the ergonomics of the activity. The intention is to propose ergonomic recommendations for the work process, since there is a lack of studies that analyze the work of health professionals who work in strategic leadership positions. The research method was content analysis, through semi-structured interviews. Adaptation of the activities developed was proposed, in the organization of work, distribution of tasks, training and qualification of the team, among other strategies to promote a healthy and safe work environment.
Keywords: hospital ergonomics; work activity; urgency and hospital emergency; hospital management